Traffic Impact Analysis Due To Surabaya Waterfront Land Development On Dr. Ir. H. Soekarno Road Intersection - Al Maheri, Muhammad Robin; Putra, Kurnia Hadi; Agusdini, Theresia Maria Chandra; Sekartadji, Ratih Sekartadji (Journal of Civil Engineering, Planning and Design, 2025)
The Surabaya City Government is currently planning a reclamation project in the coastal area of East Surabaya, specifically through the development of the Surabaya Waterfront Land area. This plan has received criticism from the public due to its potential to cause significant impacts on traffic conditions, particularly on Dr. Ir. H. Soekarno Road. The area serves as an economic growth center with dense tourism, office, and educational activities, thus causing traffic congestion that negatively impacts the economic sector. This research aims to analyze and compare the performance of four main intersections, namely Kertajaya Intersection, Dharmahusada Indah Intersection, Mulyorejo Intersection, and Kenjeran Intersection, under existing conditions and post-traffic generation due to the reclamation project. The analysis is conducted based on PKJI 2023 guidelines. The analysis results show that under existing conditions, several intersections have experienced congestion. Under post-traffic generation conditions, all intersections experience significant increases in saturation levels, even exceeding ideal capacity. Based on the traffic flow distribution results due to this generation, the construction of a 6/2 D road type (six lanes, two directions) on the Outer East Ring Road (OERR) is recommended as an alternative to reduce high vehicle volume.